Analytical investigations to evaluate bitter sensation using a taste sensing system - Gastl, Martina; Hanke, Stefan; Back, Werner (BrewingScience, 2007)
The bitter impression created by hops is a special characteristic of beer. The range of bitter units in beer is normally between 20 and 50 IBU (International Bitter Units). Apart from their preservative effects hops are used to give the beer the right bitterness and aroma. [1] The influence of hops to the aroma and flavour of beer can be enhanced by the use of hop products and pre-isomerized hop products in the brewhouse or after fermentation. Iso-alpha-acids are intensely bitter and are the main origin of bitter flavour because they are responsible for more than 75 % of beer bitterness. [2] Beside the influence of iso-alpha-acids there are many other influencing factors, which affect the sensation of bitterness. The beer matrix is very complex and as a result of those various ingredients causes matrix effects and interactions between the ingredients. The matrix effects are able to cover the bitter sensation. This is already well known by the sensorial evaluation of flavour stability and ageing effects of beer. In this case for example the hop flavour could have a positive masking effect. A search of the literature reveals that humans have an inherent preference for sweet and umami and an inherent dislike for bitter and sour. The sensory perception is not linear nor is bitterness a taste attribute which is extremely well developed in human beings (compared to herbivorous animals) and is significantly influenced by matrix effects and therefore with regard to sensory aspects there is always a discrepancy in analytical measuring and sensory evaluation. [1] In cooperation with "TecLabS" we are testing an electronic tongue (Taste Sensing System SA402B, Intelligent Sensor Technology, Inc.) with regard to bitter sensation.